1982
DOI: 10.1007/bf01033625
|View full text |Cite
|
Sign up to set email alerts
|

Urothelium-specific antibody and lectin surface mapping of bladder urothelium

Abstract: Coupled ligand-colloidal gold complexes were found to provide a convenient approach for the localization of scanning electron microscopy of cell surface membrane antigens and lectin-binding sites on bladder urothelium and for the immunocytochemical identification of urothelial cell populations at different stages of differentiation. The ligands used to prove the membrane were a urothelium-specific rabbit antibody raised to a urothelial membrane-associated antigen (UMA), and two lectins: Concanavalin A (Con A) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1982
1982
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…In the urinary tract most attention has been addressed to the urothelial cell, and in particular to blood group antigens A, B and O(H) with changes of expression of these (as well as other blood group antigens) with neoplastic transformation (Bergman and Javadpour, 1978;Lange et al, 1978;Gunter et al, 1983;Rearden et al, 1983;Summers et af., 1983). Other epithelial cell antigens have been identified on urothelial cells including urothelial membraneassociated antigen (UMA) (Hodges et al, 1982), luminal epithelial antigen (LEA) (Nathrath et at., 1979) and epithelial membrane antigen (EMA) (Pocock et al, 1983). However, despite close scrutiny of urothelial cell antigen status, little attention has been paid to accompanying lymphocyte and macrophage populations.…”
mentioning
confidence: 99%
“…In the urinary tract most attention has been addressed to the urothelial cell, and in particular to blood group antigens A, B and O(H) with changes of expression of these (as well as other blood group antigens) with neoplastic transformation (Bergman and Javadpour, 1978;Lange et al, 1978;Gunter et al, 1983;Rearden et al, 1983;Summers et af., 1983). Other epithelial cell antigens have been identified on urothelial cells including urothelial membraneassociated antigen (UMA) (Hodges et al, 1982), luminal epithelial antigen (LEA) (Nathrath et at., 1979) and epithelial membrane antigen (EMA) (Pocock et al, 1983). However, despite close scrutiny of urothelial cell antigen status, little attention has been paid to accompanying lymphocyte and macrophage populations.…”
mentioning
confidence: 99%
“…Several investigators have reported a correlation be tween morphologic differentiation and expression of spe cific molecules both in normal and neoplastic urothelium [14][15][16]. Immunohistochemical markers have been useful in our study for a more exact typing of tumor grades and a better characterization of urothelial dysplasia and carci noma in situ.…”
Section: Discussionmentioning
confidence: 85%
“…Scanning electron microscopy has demonstrated a uniform distribution of concanavalin A-binding sites over the superficial cells of the normal urothelium, attributable to cell surface membrane glycoproteins (Hodges et al 1982). Studies using the avidin-biotin complex method resulted in a weakly positive staining with concanavalin A, showing a spotty membranous pattern (Takai et al 1987).…”
Section: Lectin Bindingmentioning
confidence: 99%